Pediatric Average Volume Assured Pressure Support - Vishal Saddi; Vishal Saddi; Ganesh Thambipillay; Ganesh Thambipillay; Bradley Martin; Bradley Martin; Gregory Blecher; Gregory Blecher; Arthur Teng; Arthur Teng (Frontiers Media S.A., 2022)
Average volume assured pressure support (AVAPS) is a modality of non-invasive ventilation that enables the machine to deliver a pre-set tidal volume by adjusting the inspiratory pressure support within a set range. Data on its use in the pediatric population are limited to case reports and single centre case series. This article reviews paediatric data on use of AVAPS and highlights the need for validation to help develop specific guidelines on use of AVAPS in children.